Utilization of Coffee By-Products as Profitable Foods - A Mini Review. Issue 1 (March 2021) - Muzaifa, M; Rahmi, F; Syarifudin,
Abstract: Indonesia is one of the largest coffee producer and exporter countries in the world. The current significant environmental problem challenge being faced by Indonesian farmer is the absence of utilization of coffee by-products. Coffee processing from fruit to brewing coffee that is ready to drink produces a large amount of by-product. Depending on the processing method chosen, the waste produced also differs consisting of pulp, husk, musilage, silver skin and residual coffee grounds. This review aims to provide an overview on coffee by-products characteristic and their potential utilization as profitable products. For this purpose, we have collected and reviewed some literature on chemical properties of coffee by-products and the history of these by-products consumption in some countries. The coffee pulp is the largest by-product acquired during wet coffee processing, so the primary attention has given to the by-product. The by-products have been studied from the coffee pulp including juice, cascara and kombucha. Cascara is a tea made from dried coffee pulp. Cascara has a long history of consumption in Yemen, Ethiopia and South America with different name. Other products are still being studied as products with great potential for further development. With the high crop production projected in the future, the utilization of coffee by-products as useful products should be realized. It is hoped that the results of this review can provide insight to all stakeholders.